PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE SYNERGETIC TEACHING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Noviyanti, Lisa; Copriady, Jimmi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak: This research aimed to increase student achievement by application of active learning strategies types synergetic teaching on learning topic of Colloid in XI IPA SMAN 5 Pekanbaru. This is an experimental research with randomized control group pretest-posttest design. Subject of this research are XI IPA 3 as the experimental class, XI IPA 1 as the controll class which were determined randomly after conducting normality and homogeneity test. The experimental group was treated with the application of synergetic teaching active learning strategies while the control group without the application of synergetic teaching active learning strategies. The data analysis to test the hypothesis was using t-test right side. Based on the data analysis, it is obtaine tcount = 4,03 and ttable=1.66 with α=0,05, dk=67. tcount > ttable is 4.03> 1,66, It’s mean that the application of active learning strategies of synergetic teaching can improve students achievement on the subject of colloids in XI IPA class SMAN 5 Pekanbaru. The raising student achievement category in the experimental class including a high score by normalized gain of 0,79.Keywords: Synergetic Teaching active learning strategies, learning achievement